An empirical study of cloud computing and big data analytics. (2018) - Al-Shawakfa, Emad; Alsghaier, Hiba
The rapid growth in social media usage introduced new trends to be in line with social media technologies such as 'big data' and 'cloud computing'. Organisations collect data to use it at new levels to share accurate and stable business experimentation that direct decision makers to make brilliant decisions and help organisations make decisions in real time. These trends have also guided into a revolutionary transformation in research, invention, and business marketing. This paper highlights some aspects of big data and cloud computing with their effects on an organisation's business. Furthermore, some issues of using big data and cloud computing in various environments and the usage of cloud computing for Internet of things and issues about it were also discussed. The paper is organised into five sections: introduction, background, literature review; with subsections about Hadoop, cloud computing, and big data. Section 4 gives challenges while Section 5 gives the conclusions.